Preference and motivation tests for body tactile stimulation in fish - Gauy, Ana Carolina Dos Santos [UNESP]; Bolognesi, Marcela Cesar [UNESP]; Martins, Guilherme Delgado [UNESP]; Gonçalves-De-freitas, Eliane [UNESP] (MDPI, 2021)
We tested whether territorial fish (Nile tilapia) perceive body tactile stimulation as a positive or negative resource. Individual male fish were placed for eight days in an aquarium containing a rectangular PVC frame, which was filled with vertical plastic sticks sided with silicone bristles in the middle of the tank. Fish passing this device received a tactile stimulus. The fish then underwent a preference test by choosing between areas half-with and half-without tactile bristles. Then, fish were submitted to a motivation test where they had to pass an aversive stimulus (bright light) to access the device. Fish were, then, paired to settle social rank, which occurs by way of fights (social stressor), and were assigned again to preference and motivation tests. A group without social stress was used as a control. Contrary to our expectations, fish preferred the area without tactile bristles, although subordinate fish reached tactile stimulation more than the dominant one. Social stress did not affect the preference and motivation, suggesting that fish do not perceive tactile stimulation as a stressor reliever. However, as fish did not avoid the stimulation, reached the device spontaneously, and faced an aversive stimulus to access it, we conclude that tactile stimulation is not a negative condition and, therefore, can be used in further studies regarding fish welfare.
Keywords: Aggressive behavior; Choice; Motivation; Social stress; Welfare